Occurrence of overweight, obesity and their associated risk factors among primary school pupils in Samarra/Iraq: a cross-sectional study. - Ahmed Khalaf Al-Delaimy; Yassen Taha Sarhan; Mahasin Ali Al-Taha; Badeaa Thamer Yahyaa; Ru’ya Abdulhadi Al-Rawi (Journal of the Pakistan Medical Association, 2024)
Objective: To find the prevalence of overweight and obesity and the risk factors for increasing weight amongyoung students. Method: The cross-sectional, descriptive study was conducted during the 2018-19 academic year in Samarra, Iraq,after approval from the ethics review committee of Anbar University, Al Anbar, Iraq, and comprised primaryschoolchildren aged 7-13 years regardless of gender. After collecting sociodemographic data, based on body massindex values, the children were categorised into malnourished <5th percentile, normal 5-84th percentile,overweight 85-97th percentile, and obese greater than or equal to 97th percentile. Data was analysed using SPSS 27. Results: Of the 450 subjects, 243(54%) were girls and 207(46%) were boys. Obesity was found in 54(12%,) subjects,while 83(18.4%) were overweight. Class grades of the schoolchildren, mothers’ education, type of food taken toschool, money to buy from the school canteen, consumption of soft drinks, and eating snacks were significantlyrelated to body mass index percentile (p<0.05). Conclusion: Overweight and obesity were prevalent in school children, and a number of factors contributed to theproblem, highlighting the need for health education interventions. Key Words: Overweight, Snacks, Obesity, Risk Factors, Health, Carbonated, Beverages